ANALISIS DETERMINAN PENDAPATAN PEDAGANG PEREMPUAN DI PASAR GALIRAN KABUPATEN KLUNGKUNG - Andini, Putu Elyana; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 4 (2023): Vol.12.4.APRIL.2023[231-310], 2023)
Women tend to choose work in the informal sector in order to be able to divide their time between work, family, and also in social activities (menyama braya). One of them is by trading in traditional markets. The purpose of this study is as follows to analyze the effect of age, working hours, capital, number of family dependents, and length of business on the income of female traders in the Galiran Market, Klungkung Regency. This research design uses a quantitative method in the form of associative. The research location was carried out at Galiran Market, Klungkung Regency. The number of samples in this study was 100 respondents who were selected using the purposive sampling method, namely female traders in the Galiran market who were married. The data analysis technique used in this study consisted of descriptive statistical analysis and inferential analysis (multiple linear regression analysis). The results of the analysis show that age has a significant negative effect on income, hours worked have a significant positive effect on income, capital has a significant positive effect on income. Number of family dependents has no significant positive effect on income and length of business has a significant positive effect on income.